2021
DOI: 10.1071/hc20040
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescribing patterns of general practice registrars for infective conjunctivitis: a cross-sectional analysis

Abstract: INTRODUCTION: Over-prescription of antibiotics for common infective conditions is an important health issue. Infective conjunctivitis represents one of the most common eye-related complaints in general practice. Despite its self-limiting nature, there is evidence of frequent general practitioner (GP) antibiotic prescribing for this condition, which is inconsistent with evidence-based guidelines. AIM: To investigate the prevalence and associations of GP registrars' (trainees') prescription of antibiotics for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
8
1
Order By: Relevance
“…For example, Shekhawat et al used a patient-indication lens and included all GPs in their analysis, 25 whereas Cherry et al included only patients who visited GP registrars in their sample, resulting in distinct assessment denominators and outcomes. 55 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Shekhawat et al used a patient-indication lens and included all GPs in their analysis, 25 whereas Cherry et al included only patients who visited GP registrars in their sample, resulting in distinct assessment denominators and outcomes. 55 …”
Section: Discussionmentioning
confidence: 99%
“…For example, Shekhawat et al used a patient-indication lens and included all GPs in their analysis, while Cherry et al included only patients who visited GP registrars in their sample resulting in distinct assessment denominators and outcomes. [45,46] Our assessment of non-indicated prescribing of benzodiazepines for non-specific LBP shows that Dutch GPs mostly adhere to professional guidelines. Only 3% of patients received an inappropriate prescription, which is lower compared to the findings of recent studies from the US.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…We observed that ophthalmic antibiotics were prescribed for more than one third of patients, including a large proportion of those with viral and unspecified conjunctivitis and a smaller proportion of patients with allergic conjunctivitis, for which clinical practice guidelines do not recommend the use of antibiotics [8,9,14]. However, the rate of antibiotics prescriptions for acute conjunctivitis is higher in countries such as the USA (58.0-72.7%) [6,15], Australia (74.0%) [16], Holland (80.0%) [17] and Belgium (89.4%) [7] and lower in different Scandinavian countries (4.2-21.1%) [18]. The present analysis found that the majority of prescriptions were issued by general practitioners, which is consistent with the reports of other publications [6,[15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…21 An aspect of clinical uncertainty is that produced by the false dichotomy of viral or bacterial aetiology. As above, addressing the syndromic presentation rather than aetiological diagnosis [5][6][7][8][9][10]22 will lessen uncertainty as a driver of antibiotic prescribing in ARIs and infective conjunctivitis.…”
Section: Practitioner Clinical Uncertaintymentioning
confidence: 99%